Consistency of spatial ability performance in children, adolescents, and young adults - Morawietz, Christina; Dumalski, Nils; Wissmann, Anna Maria; Wecking, Jonas; Muehlbauer, Thomas (Frontiers in Psychology, 2024)
Background: Spatial abilities are essential cognitive skills for many aspects of our everyday life that develop substantially throughout childhood and adolescence. While there are numerous measurement tools to evaluate these abilities, many of them have been designed for specific age groups hampering comparability throughout development. Thus, we determined test-retest-reliability and minimal detectable change for a set of tests that evaluate spatial ability performance in their variety in youth and compared them to young adults.: Children (age: 11.4 ± 0.5 years, n=26), adolescents (age: 12.5 ± 0.7 years, n=22), and young adults (age: 26.1 ± 4.0 years, n=26) performed a set of five spatial ability tests twice, 20 minutes apart: Paper Folding Test (PFT), Mental Rotation Test (MRT), Water Level Task (WLT), Corsi Block Test (CBT), and Numbered Cones Run (NCR). Relative and absolute testretest reliability was determined by calculating the intraclass correlation coefficient (ICC3,1)and the standard error of measurement (SEM), respectively. Further, the minimal detectable change (MDC95%) was calculated to identify clinically relevant changes between repeated measurements.Results: Irrespective of test, reliability was "excellent" (i.e., ICC3,1 ≥ 0.75) in all age cohorts and the SEM values were rather small. The MDC95% values needed to identify relevant changes in repeated measurements of spatial ability performance ranged between 0.8 and 13.9% in children, 1.1 and 24.5% in adolescents, and 0.7 and 20.8% in young adults.The determined values indicate that the investigated set of tests is reliable to detect spatial ability performance in healthy children, adolescents, and young adults.